A 40 Gb/s Chip-to-Chip Interconnect for 8-Socket Direct Connectivity Using Integrated Photonics - Stelios Pitris; Miltiadis Moralis-Pegios; Theonitsa Alexoudi; Joris Lambrecht; Xin Yin; Johan Bauwelinck; Yoojin Ban; Peter De Heyn; Marianna Pantouvaki; Joris Van Campenhout; Ronald Broeke; Nikos Pleros (IEEE Photonics Journal)
We present an O-band any-to-any chip-to-chip (C2C) interconnection at 40 Gb/s suitable for up to 8-socket direct connectivity in multi-socket server boards, utilizing integrated low-energy photonics for the transceiver and routing functions. The C2C interconnect exploits an Si-based ring modulator as its transmitter and a co-packaged photodiode/transimpedance amplifier enabled receiver interconnected over an 8 × 8 Si-based arrayed waveguide grating router, allowing for a single-hop flat-topology interconnection between eight nodes. A proof-of-concept demonstration of the C2C interconnect is presented at 25 and 40 Gb/s for eight possible routing scenarios, revealing clear eye diagrams at both data rates with extinction ratios of 4.8 ± 0.3 and 4.38 ± 0.31 dB, respectively, among the eight routed signals.